Lactation Stage-Dependency of the Sow Milk Microbiota - Chen, Wei; Mi, Jiandui; Lv, Ning; Gao, Jinming; Cheng, Jian; Wu, Ruiting; Ma, Jingyun; Lan, Tian; Liao, Xindi (Frontiers in Microbiology, 2018)
Breast milk is essential for the initial development of neonatal animals, as it provides not only essential nutrients and a broad range of bioactive compounds but also commensal bacteria. The milk microbiota contributes to the “initial” intestinal microbiota of infants and also plays a crucial role in modulating and influencing neonatal health. However, the milk microbiota of sows has yet to be systematically investigated. The goal of the present study was to characterize variations in bacterial diversity and composition in sow milk over the duration of lactation using a high-throughput sequencing approach. Milk samples (n = 160) were collected from 20 healthy sows at eight different time points, and microbial profiles were analyzed by 16S ribosomal RNA (rRNA) sequencing using the Illumina MiSeq platform. The composition and diversity of the milk microbiota changed significantly in colostrum but was relatively stable in transitional and mature milk. Firmicutes and Proteobacteria were the most dominant phyla in sow milk. The relative abundances of the two most dominant bacterial genera, Corynebacterium and Streptococcus, were significantly higher in colostrum than in transitional milk and mature milk samples, and the other four most dominant bacterial taxa (Lactobacillus, two unclassified genera in the families Ruminococcaceae and Lachnospiraceae, and an unclassified genus in the order Clostridiales) demonstrated higher relative abundances in transitional and mature milk than in colostrum. Membrane transport, amino acid metabolism and carbohydrate metabolism were the most abundant functional categories in sow milk communities. Microbial network analysis based on the predominant genera revealed that the abundance of Helcococcus was negatively correlated with the abundances of most other genera in sow milk. Our results are the first to systematically indicate that the sow milk microbiota is a dynamic ecosystem in which changes mainly occur in the colostrum and remain generally stable throughout lactation.